Bis‐Diketopyrrolopyrrole Moiety as a Promising Building Block to Enable Balanced Ambipolar Polymers for Flexible Transistors. Issue 22 (29th March 2017) - Yang, Jie; Wang, Hanlin; Chen, Jinyang; Huang, Jianyao; Jiang, Yingying; Zhang, Jianqi; Shi, Longxian; Sun, Yunlong; Wei, Zhixiang; Yu, Gui; Guo, Yunlong; Wang, Shuai; et al.
Abstract : A bis‐diketopyrrolopyrrole (DPP dimer, 2DPP) core is synthesized with much stronger electron deficiency than DPP by homocoupling of DPP. 2DPP‐based polymers, P2DPP‐BT, P2DPP‐TT, P2DPP‐TVT, and P2DPP‐BDT, are obtained. Top‐gated organic field‐effect transistors on plastic substrate are fabricated. Compared with their mono‐DPP‐based polymers, remarkable improvement of electron mobilities of P2DPPs is achieved. Meanwhile, their p‐channel performance becomes higher. Abstract : A bis‐diketopyrrolopyrrole (DPP dimer, 2DPP) core is synthesized with much stronger electron deficiency than DPP by homocoupling of DPP. 2DPP‐based polymers, P2DPP‐BT, P2DPP‐TT, P2DPP‐TVT, and P2DPP‐BDT, are obtained. Top‐gated organic field‐effect transistors are fabricated on plastic substrates. Compared with their mono‐DPP‐based polymers, remarkable improvement of electron mobilities of P2DPPs is achieved. Meanwhile, their p‐channel performance becomes higher.